Plasma osteopontin in acute liver failure - Srungaram, Praveen; Rule, Jody A.; Yuan, He Jun; Reimold, Andreas; Dahl, Benny; Sanders, Corron; Lee, William M. (Cytokine (Philadelphia, Pa.), 2015)
•Osteopontin (OPN) is a cytokine that is elevated in settings associated with inflammation.•Plasma OPN levels in acute liver failure patients were increased from 10- to 500-fold over normal.•OPN levels in acute or chronic inflammation (RA, post-op) were only minimally elevated.•Highest OPN values occurred with severe hepatocyte necrosis (acetaminophen or ischemia).•The significance of OPN release remains to be determined, it may play a cytoprotective role. Osteopontin (OPN) is a novel phosphoglycoprotein expressed in Kupffer cells that plays a pivotal role in activating natural killer cells, neutrophils and macrophages. Measuring plasma OPN levels in patients with acute liver failure (ALF) might provide insights into OPN function in the setting of massive hepatocyte injury. OPN levels were measured using a Quantikine® ELISA assay on plasma from 105 consecutive ALF patients enrolled by the US Acute Liver Failure Study Group, as well as controls including 40 with rheumatoid arthritis (RA) and 35 healthy subjects both before, and 1 and 3days after undergoing spine fusion (SF) surgery as a model for acute inflammation. Median plasma OPN levels across all etiologies of ALF patients were elevated 10- to 30-fold: overall median 1055ng/mL; range: 33–19,127), when compared to healthy controls (median in pre-SF patients: 41ng/mL; range 2.6–86.4). RA and SF post op patients had elevated OPN levels (37ng/mL and 198ng/mL respectively), well below those of the ALF patients. Median OPN levels were highest in acetaminophen (3603ng/mL) and ischemia-related ALF (4102ng/mL) as opposed to viral hepatitis (706ng/mL), drug-induced liver injury (353ng/mL) or autoimmune hepatitis (436ng/mL), correlating with the degree of hepatocellular damage, as reflected by aminotransferase values (R value: 0.47 for AST, p<0.001). OPN levels appeared to correlate with degree of liver necrosis in ALF. Very high levels were associated with hyperacute injury and good outcomes. Whether OPN exerts a protective effect in limiting disease progression in this setting remains uncertain.